Reformasi Arab Saudi di Masa Kepemimpinan Faisal bin Abdul Aziz (1964-1975) - Ikhsan, Daffa Agussandy; Putri, Ida; Darojat, Zakiya (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta, 2023)
This research examines the reforms that took place in Saudi Arabia after Faisal bin Abdul Aziz ascended to the throne as the king. The aim of this study is to explain the policies implemented by King Faisal bin Abdul Aziz during his reign as the King of the Kingdom of Saudi Arabia (1964 - 1975). The research method employed is historical research, which involves source collection, source criticism, interpretation, and writing.The findings of this research indicate that Faisal bin Abdul Aziz officially ascended to the throne as the King of Saudi Arabia in 1964. During his reign, Faisal bin Abdul Aziz implemented various policies that brought about significant changes in the Kingdom of Saudi Arabia. Faisal initiated reform efforts to modernize Saudi society and transform various aspects of the country. Furthermore, the policies implemented by King Faisal bin Abdul Aziz played a role in triggering changes in various sectors of the Saudi Arabian Kingdom, including education, foreign policy, and law. Abstrak :Penelitian ini membahas mengenai Reformasi yang terjadi di Arab Saudi setelah Faisal bin Abdul Aziz naik tahta sebagai raja. Penelitian ini bertujuan untuk menjelaskan kebijakan-kebijakan yang dilakukan oleh Raja Faishal bin Abdul Aziz selama masa beliau menjabat sebagai raja Kerajaan Arab Saudi (1964 – 1975). Metode penelitian menggunakan metode sejarah, yang dimulai dari pengumpulan sumber, kritik sumber, interpretasi, dan penulisan.Hasil penelitian ini menunjukkan bahwa Faisal bin Abdul Aziz secara resmi naik tahta sebagai raja Arab Saudi pada tahun 1964. Dalam masa kekuasaannya, Faisal bin Abdul Aziz melakukan berbagai kebijakan yang berdampak pada perubahan dalam Kerajaan Arab Saudi. Faisal menjalankan usaha reformasi untuk mulai membawa masyarakat Arab Saudi ke arah kehidupan modern dan mengubah berbagai aspek yang ada di dalam negara. Lebih lanjut, kebijakan-kebijakan yang dilakukan oleh Raja Faisal bin Abdul Aziz berperan dalam memicu perubahan Kerajaan Arab Saudi di berbagai sektor termasuk pendidikan, politik luar negeri, hukum.